2022
DOI: 10.1111/jcpt.13779
|View full text |Cite
|
Sign up to set email alerts
|

Rapid infusion of infliximab biosimilars and the incidence and severity of infusion‐related reactions in patients with inflammatory bowel disease

Abstract: What Is Known and Objective: Infliximab is an anti-tumour necrosis factor agent used in the treatment of inflammatory bowel disease (IBD), which includes Crohn's disease and ulcerative colitis. While the use of infliximab is well established in the treatment of IBD, there are now four recently FDA-approved infliximab biosimilars that are increasingly used due to their cost-benefit for patients, institutions and payors. In addition, shortening the length of infliximab infusions from 120 min (standard infusion) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Therefore, an association between biosimilar use and the occurrence of IR could not be assessed. However, previous studies in children and adults with IBD showed that switching from IFX to biosimilar CT-P13 was not associated with an increase in IR (41,42). The lack of randomization has led to multiple differences in the baseline characteristics between the patient groups, which could have influenced the primary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an association between biosimilar use and the occurrence of IR could not be assessed. However, previous studies in children and adults with IBD showed that switching from IFX to biosimilar CT-P13 was not associated with an increase in IR (41,42). The lack of randomization has led to multiple differences in the baseline characteristics between the patient groups, which could have influenced the primary outcome.…”
Section: Discussionmentioning
confidence: 99%